Peer and Self Editing Strategies to Improve Students’ Writing Skill - Winarto, Agus Edi (JEELS (Journal of English Education and Linguistics Studies), 2018)
Peer and self editing strategies are social and metacognitive strategies used in the steps of sharing, revising, and editing in writing. The objective of the study is to see how peer and self editing strategies are able to improve students’ writing skill. 64 students participants were actively involved in this classroom action research. Peer editing worksheet, self editing worksheet, and test sheet were used as the instruments. The results showed that students’ writing skill improved in all elements: the quality of format, punctuation and mechanics, content, organization, and grammar and sentence structure. They had achieved the criteria of success as determined. It can be concluded that peer and self-editing strategies are able to improve students’ writing skill.